Analisis Pengarsipan Digital Jaringan Dokumen Informasi Hukum (JDIH) di Kantor KPU Provinsi Bengkulu - Ujang Juhardi; Adelia Karolina; Ariski Munandar; Muhammad Renaldi; Widia Seprianti (Jurnal Dehasen Untuk Negeri, 2022)
The management of the Bengkulu Province KPU's Legal Documentation and Information Network (JDIH) began in February 2019 which was marked by the formation of a team based on the decision of the Bengkulu Province general election commission Number: 16/HK.03.1-Kpt/Prov/17/11/2019 regarding team composition Legal Documentation and Information Network (JDIH) at the General Election Commission of Bengkulu Province. The Legal Documentation and Information Network is a decision on the management of Legal Documentation and Information regarding technical guidelines for the management of Legal Documentation and Information within the General Election Commission (KPU, Regency/City). 2021 amounted to 191. The system used in the technical sub-section of election administration, participation, public relations, and human resources has been well programmed. On the Bengkulu Provincial KPU JDIH website page, there are KPU regulations, decisions which include (Provincial KPU Decisions and Regency/City Decisions). Data collection techniques in this journal were obtained from literature and were participatory in the activities of the Bengkulu Province KPU office. The results obtained from this activity can determine the comparison of the number of viewers and the number of PKPU that has been determined.